Development Of An Integrated Recovery Process For Recombinant Hepatitis B Core Antigen - Ho, Chin Woi (2007)

(untitled)
Hepatitis B core antigen (HBcAg) expressed intracellularly in Escherichia coli (E. coli) has great potential and high demand in pharmaceutical market. The main objective of this study was to develop an efficient and cost effective protocol for the recovery of recombinant HBcAg. Cell disruption is the prerequisite step to release the intracellular HBcAg to the surrounding medium prior to subsequent purification processes. In the current study, E. coli was disrupted by mechanical method of bead milling. Bead milling can be operated either in batch or continuous recycling mode. The performance of bead milling is affected by parameters such as impeller tip speed, biomass concentration, bead loading and feed flow rate. Thus, in the first chapter of the study, the effects of these parameters on different modes of operation were investigated. The effect of these operation modes on the subsequent downstream processing was also examined. In the second chapter of the study, a purification protocol for the recovery of HBcAg was developed. The HBcAg was initially purified by the integrated operation of batch mode bead milling and expanded bed adsorption (EBA), and subsequently purified by size exclusion chromatography (SEC). The results of the cell disruption study show that the optimum disruption of E. coli and release of intracellular HBcAg in batch mode bead milling was achieved at impeller tip speed of 14 m/s, biomass concentration of 20% (w/v) and bead loading of 80% (v/v), whilst the performance of continuous recycling bead milling was peak at impeller tip speed of 14 m/s, biomass concentration of 10% (w/v) and feed flow rate of 15 L/h. Batch mode was ideal for the batch anion-exchange adsorption, in which a HBcAg yield of 34.3%, a HBcAg purity of 65% and a purification factor of 2.86 was achieved. In the purification study, the product yield, product purity and purification factor achieved in the integrated EBA process was 55%, 42.3% and 1.96, respectively. The partially purified HBcAg was then further purified by SEC, in which a product yield of 42.4% was obtained. The SEC purification has also yielded a HBcAg purity of 88.2%, which corresponded to a purification factor of 4.08. The purified HBcAg was confirmed to be functionally active and hence, can be used in the development of hepatitis B virus (HBV) diagnostic kits.